(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe people’s knowledge, attitudes towards preventing and controlling harmful effects of pesticides on human health at Huu Hoa commune, Thanh Tri district, Hanoi city in 2024 and identify related factors. Subject and methods: A cross-sectional study was conducted on 200 people aged 18 and older from September to December 2024. Results: Results showed that only 35.5% of respondents had good knowledge of preventing and controlling harmful effects of pesticides on human health and merely 30.5% exhibited a possitive attitude. In this study, attitude towards preventing and controlling harmful effects of pesticides on human health was significantly associated (p < 0.05) with educational levels; overall good knowledge of preventing and controlling harmful effects of pesticides on human health; know the impact of pesticides on the environment; know the action to be taken after pesticide exposure; know the routes of pesticide exposure into the body. Conclusion: Generally, the knowledge and attitudes of people on pesticides was poor. The findings of this study underline the need to train people concerning the safe and proper use of pesticides to minimize hazards to human health and the environment.